Peripheral Immune Dysfunction in ESCC with Lymph Node Metastasis: Implications for Preoperative Diagnosis and Prognosis - Yingcen Li; Bin Li; Helian Li; Jingyan Xu; Yali Luo; Jian Gao; Jingxuan Han; Xuling Han; Yiran Zhao; Alin Zhang; Feng Qian (Phenomics, 2026)

Research progress and prospects on refractory materials prepared from high-carbon ferrochrome slag: A review - Zhiqiang Yang; Zhiyun Ji; Xiaohui Fan; Min Gan; Qiang Li; Yuanjie Zhao; Xiaoxian Huang; Zengqing Sun; Xuling Chen; Zhenxiang Feng (Process Safety and Environmental Protection, 2026)

Disentangling meteorological and emission drivers of PM2.5 and bridging the gap to WHO guideline: A case study in an underdeveloped ethnic minority County in Southwest China - Xuling Ma; Yanlin Chu; Yi Li; Ying Wang; Weili Lin (Air Quality, Atmosphere & Health, 2026)

Multiligand growth modulation of metal–organic frameworks for the detoxification of composite nanofabrics for chemical warfare agents - Weiguang Yan; Baokang Yu; Xiang Li; Gaorui Feng; Shiliang Sheng; Yanru Bai; Xianglong Zheng; Yanlai Feng; Xiaolong Hao; Rongwu Wang; Xuling Jin; Jianxin He (Chemical Engineering Journal, 2025)

PICK1 modulates the proliferation and migration of gastric cancer cells by regulating TLR4 - Kaiqiang Li; Yimin Yang; Yaling Wang; Jing Jin; Qianni Wang; Lina Peng; Aibo Xu; Xuling Luo; Wei Yang; Peng Xu; Bingyu Chen; Ke Hao; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Humidity-responsive PCL/ICs/PVA pad with directional water transport for fruit preservation - Xuling Song; Zhengfeng Wang; Minxin Zhou; Yuwei Li; Yujie Wei; Yi Luo; Jianfeng Li; Bei Xu; Baijun Shang; Qingshan Duan (Chemical Engineering Journal, 2025)

Highly ammonia-sensitive triboelectric materials enabled by gas-sensing enhancement effect - Yi Luo; Jianfeng Li; Juanxia He; Xuling Song; Bei Xu; Zhijun Zhang; Jiamin Zhao; Yuxin Xie; Yaqi Zhang; Zhengfeng Wang; Baijun Shang; Minxin Zhou; et al. (Chemical Engineering Journal, 2025)

Map-based cloning revealed BhAPRR2 gene regulating the black peel formation of mature fruit in wax gourd (Benincasa hispida) - Xuling Zhai; Jinqiang Yan; Wenrui Liu; Zheng Li; Zhenqiang Cao; Ying Deng; Renlian Mo; Baochen Wang; Xiaoxin Cheng; Dasen Xie; Biao Jiang (Theoretical and Applied Genetics, 2025)

Bionic wood-inspired structure enables aerogel film triboelectric material with humidity adaptation - Ye Zhang; Zhijun Zhang; Weiqing Peng; Juanxia He; Bei Xu; Xuling Song; Jianfeng Li; Yi Luo; Shuangxi Nie; Shuangfei Wang; Dongwu Liang; Qingshan Duan (Chemical Engineering Journal, 2024)

Correction: Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2024)

Self-standing CdS/TiO2 Janus nanofiberous membrane: COD removal, antibacterial activity and photocatalytic degradation of organic pollutants - Shiva Pandeya; Rui Ding; Yufei Ma; Xuling Han; Meixing Gui; Purnima Mulmi; Khim Prasad Panthi; Bhanu Bhakta Neupane; Hem Raj Pant; Ziliang Li; Mahesh Kumar Joshi (Journal of Environmental Chemical Engineering, 2024)

Death-associated protein 3 in cell death and beyond - Ting Cao; Xuling Luo; Binjiao Zheng; Yao Deng; Yu Zhang; Yuyan Li; Wenwen Xi; Meng Guo; Xuefeng Yang; Zhiyue Li; Bin Lu (Genome Instability & Disease, 2024)

Analysis of the Immune Response by Standardized Whole-Blood Stimulation with Metabolism Modulation - Jialin Zhao; Xuling Han; Helian Li; Yali Luo; Yan Fang; Yun Wang; Jian Gao; Yiran Zhao; Jingxuan Han; Feng Qian (Phenomics, 2024)

Flexible and MOF-808 uniformly assembled polyimide nanofiber membranes with excellent mechanical properties for rapid degradation of chemical warfare agents - Zhikang Cheng; Xiang Li; Li Zhang; Zupei Yuan; Haimin Zheng; Hao Guo; Xu Zhao; Jie Chen; Yu Pan; Xiaoxiao Chen; Yanlai Feng; Zhouai Luo; et al. (Chemical Engineering Journal, 2023)

Comprehensive evaluation of hydrogen-rich energy application in iron ore sintering process: Deep function mechanism analysis and process optimization - Yufeng Wu; Xiaohui Fan; Zhiyun Ji; Min Gan; Dan Yu; Zengqing Sun; Xuling Chen; Lincheng Liu; Xiaoxian Huang; Jinhua Li (Journal of Cleaner Production, 2023)

Threat of soil formation rate to health of karst ecosystem - Chen Ran; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Yue Cao; Luhua Wu; Fei Chen; Chaojun Li; Xuling Luo; Min Liu; Sirui Zhang (Science of The Total Environment, 2023)

Deep Immunophenotyping of Human Whole Blood by Standardized Multi-parametric Flow Cytometry Analyses - Jian Gao; Yali Luo; Helian Li; Yiran Zhao; Jialin Zhao; Xuling Han; Jingxuan Han; Huiqin Lin; Feng Qian (Phenomics, 2023)
Immunophenotyping is proving crucial to understanding the role of the immune system in health and disease. High-throughput flow cytometry has been used extensively to reveal changes in immune cell composition and function at the single-cell level. Here, we describe six optimized 11-color flow cytometry panels for deep immunophenotyping of human whole blood. A total of 51 surface antibodies, which are readily available and validated, were selected to identify the key immune cell populations and evaluate their functional state in a single assay. The gating strategies for effective flow cytometry data analysis are included in the protocol. To ensure data reproducibility, we provide detailed procedures in three parts, including (1) instrument characterization and detector gain optimization, (2) antibody titration and sample staining, and (3) data acquisition and quality checks. This standardized approach has been applied to a variety of donors for a better understanding of the complexity of the human immune system.

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

Investigation on the application of by-product steam in iron ore sintering: performance and function mechanism - Yufeng Wu; Xiaohui Fan; Zhiyun Ji; Min Gan; Haoyu Zhou; Haorui Li; Xuling Chen; Yuanjie Zhao; Rongchang Zhang; Ruisi Lai (Environmental Science and Pollution Research, 2022)

High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes - Chaojun Li; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Luhua Wu; Fei Chen; Huipeng Xi; Xuling Luo; Chen Ran; Huan Chen; Sirui Zhang; Min Liu; et al. (Global Change Biology, 2022)
Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO 2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSF α ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSF α . We found that the total SCSF α was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSF α in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSF α was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSF α to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle.

A New Indicator for Global Food Security Assessment: Harvested Area Rather Than Cropland Area - Fengjiao Song; Shijie Wang; Xiaoyong Bai; Luhua Wu; Jinfeng Wang; Chaojun Li; Huan Chen; Xuling Luo; Huipeng Xi; Sirui Zhang; Guofeng Luo; Mengqi Yan; et al. (Chinese Geographical Science, 2022)

Telephone Follow-up Design and Practice for Advanced Cancer Pain Patients - Benyan Zou; Xuling Li; Xuxia Huang; Dandan Xiong; Yu Liu (Journal of Cancer Education, 2020)

The effects of Japanese encephalitis virus antibodies on Zika virus infection - Xiaoen He; Xinyue Lang; Jianhai Yu; Li Zhu; Zhiran Qin; Xuling Liu; Pei Chen; Chengguqiu Dai; Tingting Chen; Xujuan Li; Yangyang Chen; Dongrui Zhou; et al. (Medical Microbiology and Immunology, 2020)

Characteristics and complete genome sequence of the virulent Vibrio alginolyticus phage VAP7, isolated in Hainan, China - Mingming Gao; Yanhong Qin; Hang Fan; Xianglilan Zhang; Puyuan Li; Huiying Liu; Guangqian Pei; Zhiqiang Mi; Xuling Xu; Yigang Tong; Changqing Bai (Archives of Virology, 2020)

Interactions Between α-Synuclein and Tau Protein: Implications to Neurodegenerative Disorders - Xuling Li; Simon James; Peng Lei (Journal of Molecular Neuroscience, 2016)

CLU rs9331888 Polymorphism Contributes to Alzheimer’s Disease Susceptibility in Caucasian But Not East Asian Populations - Shuyan Zhang; Xuling Li; Guoda Ma; Yongshuai Jiang; Mingzhi Liao; Rennan Feng; Liangcai Zhang; Jiafeng Liu; Guangyu Wang; Bin Zhao; Qinghua Jiang; Keshen Li; et al. (Molecular Neurobiology, 2016)

Epithelial sodium channel enhanced osteogenesis via cGMP/PKGII/ENaC signaling in rat osteoblast - Jun Chen; Hengjie Zhang; Xuling Zhang; Guozhu Yang; Li Lu; Xingyan Lu; Chao Wan; Kosei Ijiri; Honglong Ji; Qingnan Li (Molecular Biology Reports, 2014)